The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/srep15575
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Suppresses Bovine Viral Diarrhoea Virus Replication in vitro

Abstract: Viral cycle progression depends upon host-cell processes in infected cells, and this is true for bovine viral diarrhoea virus (BVDV), the causative agent of BVD that is a worldwide threat to the bovine industry. Heme oxygenase-1 (HO-1) is a ubiquitously expressed inducible isoform of the first and rate-limiting enzyme for heme degradation. Recent studies have demonstrated that HO-1 has significant antiviral properties, inhibiting the replication of viruses such as ebola virus, human immunodeficiency virus, hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Additionally, it also works as a strong negative regulator in the development of oxidative stress, which is upregulated by many signaling pathways7, and its protection has been confirmed in myocardial ischemia-reperfusion injury, hepatic injury, brain hemorrhage, acute kidney injury and viral diarrhea8. Our previous findings showed strong evidence that HO-1 upregulation plays a pivotal role in the defense against oxidative stress and acts as a critical mediator of cellular homeostasis.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Additionally, it also works as a strong negative regulator in the development of oxidative stress, which is upregulated by many signaling pathways7, and its protection has been confirmed in myocardial ischemia-reperfusion injury, hepatic injury, brain hemorrhage, acute kidney injury and viral diarrhea8. Our previous findings showed strong evidence that HO-1 upregulation plays a pivotal role in the defense against oxidative stress and acts as a critical mediator of cellular homeostasis.…”
mentioning
confidence: 75%
“…The induction of HO-1 occurs as an adaptive and beneficial response in many varied tissues and cellular injury models including sepsis, ischemia reperfusion, hyperoxia, hypoxia, and other oxidative stress28. Our previous studies also showed that the induction of HO-1 by LPS has a protective effect on the lung, kidney and liver8928. Recently, studies have shown that the mechanism is likely regulated via the NF-κB and Nrf2/HO-1 signaling pathway29.…”
Section: Discussionmentioning
confidence: 98%
“…Enhanced HO-1 expression inhibits replication of many viruses, including HIV-1, Ebola virus, hepatitis B virus (HBV), and hepatitis C virus (HCV) (11)(12)(13)(14). Our previous work showed that overexpression or induction of HO-1 expression inhibits PRRSV and bovine viral diarrhea virus (BVDV) replication (15,16). Furthermore, microRNA miR-24-3p promotes PRRSV replication through suppression of HO-1 expression (17), indicating that increased expression of HO-1 may provide a potential new antiviral strategy against PRRSV infection.…”
mentioning
confidence: 99%
“…Heme oxygenase-1 (HO-1) breaks down heme to biliverdin, carbon monoxide (CO) and ferrous iron 13 . It has been reported that HO-1 can mediate cytoprotective effects under inflammatory conditions, and induction of HO-1 is thought to be an adaptive cellular response against stress 14 .…”
mentioning
confidence: 99%